(untitled) (Journal of the College of Basic Education, 2022)
The study dealt with the spatial variation of the (secondary) school occupancy rate and its effect on educational levels in the center of Baquba city, which is located in Diyala governorate in the center of Baquba district. It covers an area of ​​54,314 km 2 and extends between 40 O33-37 O33 And linear length (34 O44 and 43 O44) eastward. The study found that factors affecting the geographical distribution of students and institutions of secondary education are (population size, transport routes, economic, social and cultural factors), and their impact on the distribution of students and educational institutions that affected students’ education, Of the impact in terms of the laws and procedures used in educational policy. There is a difference in the spatial distribution of secondary schools in most neighborhoods of the city. The largest share of secondary schools was for girls with 12 schools. The schools for boys were 9 schools and there was one mixed school. It has not had a share of secondary education, as well as the number of students varies between the schools of the districts of Baquba. In some schools it has been a positive indicator in comparison with the Iraqi standard (460 students) for one school (Al-Farakd for Girls, Al-Hassan bin Ali for Boys, Girl Friendly, Girls Evening Nawras, Al-Hurriya for Girls, Jumana for Girls, Tarfa Bin Al Abd for Boys, Women Mixed, Nizar Boys) The number of students is more than the Iraqi standard, and the number of students is more than the Iraqi standard, This is a negative indicator affecting the educational level of students as well as the efficiency of the teaching staff. The number of teaching staff in the city of Baquba ranked first, with 708 teachers and schools out of (2142) teachers and schools for each judiciary. The number of people in the city includes 271 study departments, 101 of which are girls’ ), A boys’ education division and (7) mixed study people. This is due to the difference in the number of students among the schools in the city of Baquba. As for the number of students / teachers in most of the schools in Baquba, it is a positive indicator compared to the Iraqi standard, except for the schools of Aisha for girls, Najaf for boys, the most trusted link for girls. This was due to the increase in the number of students in some of them and the low number of teaching staff. As indicated by the standards of the school and the appropriateness of school buildings, all schools in the city of Baquba dedicated to the construction of teachers and their return to the government, and most schools are occupied by two schools, which number (18) and two schools operated by one school only, and there are two schools operated by three schools (Adnanieh girls and Fatima for girls) (9) schools need to be renovated (Al-Farqad for Girls, Al-Moalemeen neighborhood, Al-Adnanieh for Girls, Nizar for Boys, Al-Salam for Boys, Aisha for Girls, Evening Nawras, (13) valid Education